(untitled) (Indian Journal of Nematology, 2024)
The comparative nematicidal activity of 12 nanoparticles (NPs) viz., cobalt ferrite (CoFe2O4), elemental copper (Cu-), ferric oxide (Fe2O3), nickel ferrite (NiFe2O4), nickel peroxide (NiO2), Polyaniline (PANI), Polyaniline + ferrite (P600), tin oxide (SnO2), titanium oxide (TiO2), zinc ferrite (ZnFe2O4), zinc oxide (ZnO), zinc peroxide (ZnO2), and salicylic acid (SA) were evaluated against root-knot nematode, Meloidogyne javanica. In vitro screening of NPs and SA at 5 µg/mL, 10 µg/mL, 15 µg/mL, 20 µg/mL, and 25 µg/mL revealed considerable variability in inhibiting the hatching of eggs and causing mortality of M. javanica juveniles. In general, the NPs that caused significant inhibition in hatching also caused maximum mortality, and their effectiveness increased with the increasing concentrations. Among the NPs, zinc peroxide (20 µg/mL), salicylic acid (20 µg/mL), zinc oxide (20 µg/mL), elemental copper (20 µg/mL), nickel peroxide (25 µg/mL) and ferric oxide (25 µg/mL) caused the greatest inhibition in the hatching with 100 per cent mortality of M. javanica J2. Overall effectiveness of NPs and SA on the egg hatching and mortality of M. javanica at 20 µg/mL were in order of: Zinc peroxide > Salicylic acid > Zinc oxide > Elemental copper > Nickel peroxide > Ferric oxide > Tin oxide > Titanium oxide > Polyaniline > Polyaniline + ferrite > Cobalt ferrite > Zinc ferrite > Nickel ferrite.